2022
DOI: 10.1108/bfj-02-2022-0120
|View full text |Cite
|
Sign up to set email alerts
|

Organic food and obesity: factors influencing actual purchase of organic food in COVID-19 pandemic with moderating role of organic food availability

Abstract: PurposeOrganic food consumption decreases the risk of becoming obese or overweight. This study intends to see the influence of customer perceived value, COVID-19 fear, food neophobia, effort and natural content on the intention to purchase organic food (IPOF) that leads to the actual purchase of organic food (APOF). Moreover, organic food availability is a moderator between IPOF and APOF.Design/methodology/approachPLS-SEM is used for hypothesis testing. A purposive sampling technique was followed to gather dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 112 publications
1
10
0
Order By: Relevance
“…Food neophobia is negatively related to satisfaction toward organic food and accepted H3. Nguyen et al (2022) reveal that food neophobia is negatively linked to organic food liking. This study suggests that organic food companies can develop trust among customers that avoid buying organic food by conveying organic food advantages.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Food neophobia is negatively related to satisfaction toward organic food and accepted H3. Nguyen et al (2022) reveal that food neophobia is negatively linked to organic food liking. This study suggests that organic food companies can develop trust among customers that avoid buying organic food by conveying organic food advantages.…”
Section: Discussionmentioning
confidence: 93%
“…The major reason to purchase organic food is health ( Colovi c and Miti c, 2022). Customers are more conscious during the COVID-19 pandemic about health and they increase their consumption of organic food instead of inorganic food (Nguyen et al, 2022). Young consumers are more health-conscious and try to purchase organic food (Pham et al, 2019).…”
Section: Health Consciousness and Satisfaction Toward Organic Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also suggested that the relationship between the intention to (re)purchase organic products with knowledge of the product and other moderators be tested, such as, for example, purchase frequency, age, age group of the consumer, type of organic food, among other demographic aspects, in addition to testing mediators such as product availability, cultural aspects and definition of brands (from agricultural producers or retailers) that can influence the decision to (re)purchase organic foods. Furthermore, it would also be opportune to investigate the moderating effect of organic food availability (Nguyen et al. , 2023) and price sensitivity (Hartono et al ., 2020) on organic food purchase intention in several contexts (markets and cultures).…”
Section: Discussionmentioning
confidence: 99%
“…When normality assumptions are not fulfilled, PLS is considered an appropriate approach. The PLS-SEM technique handles both simple and complex models (Nguyen et al ., 2022). Furthermore, when data are limited, multicollinearity issues exist, and data have some missing values, the results generated by the PLS model are deemed more accurate compared to the ordinary least square (OLS) model (Rehman et al ., 2021f).…”
Section: Methodsmentioning
confidence: 99%